PERBANDINGAN PEMBELAJARAN KONVENSIONAL DAN PEMBELAJARAN BERBASIS MASALAH TERHADAP TITIK JENUH SISWA MAUPUN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Nella Kresma, Eka (Educatio Vitae, 2014)
This research aims to determine: (1) which has the lower is students saturation degree between conventional learning and problem based learning with learning mathematics.(2) which has the higher is students learning achievement between conventional learning and problem based learning with learning mathematics.This research is a quantitative research with pre-experintal design. This research was conducted of SMP N Madiun in academic year 2013/2014 in odd semester. The population was the students of class VIII at SMPN 4 Madiun. While the samples for the research were class VIII D and VIII E. The research applied test methods and questionnaire methods for the data collection. The instrument used in this research is used to learn mathematics achievement test and questionnaire for the students saturation to mathematics learning. Learning achievement test is used to determine the learning achievement in mathematics. In this research the students with problem based learning (class VIII D) is (n1) = 29 and with conventional learning (class VIII E) is (n2) = 28. Based on the analysis of data obtained: (1) for the students saturation in learning mathematics with average ( 1) = - 0,8966 the standard deviation is (s1) = 2,41046 and the average ( 2) = 0,14286 thestandard deviation is (s2) = 2,6206 with the significant level is 0,05. Based on the statistical analysis it can be conclude that the degree of students saturation in learning mathematics with problem based learning is not less than the students who are taught conventional learning. (2) for students learning achievement test the average ( 1) = 26,67 the standard deviation is (s1) = 19,4987 and the average ( 2) = 17,5 thestandard deviation is (s2) = 15,466 with the significant level is 0,05. Based on the statistical analysis it can be conclude that the students achievement who are taught by problem based learning is higher those who are taught by conventional learning.